Delphi Research Methodology Applied to Place-Based Watershed Education - Rosanna R. Vallor; Kimberly A. Yates; Michael Brody (MDPI AG, 2016)
This research focuses on the results of the Flathead Watershed Delphi survey, a consensus-building methodology used to establish foundational knowledge, skills and dispositions for the Flathead Watershed Educators Guide, a place-based watershed curriculum for middle school grades based on the Flathead Watershed Sourcebook. Survey participants (n = 33) were chosen based on their expertise as educators, resource managers and scientists living and practicing in the Flathead Watershed in northwestern Montana, USA. Participants' responses were gathered through a three-round survey conducted by the Montana State University (MSU) research team using MSU's online course management system, Desire 2 Learn (D2L), an anonymous, asynchronous platform with distance accessibility. Round One responses gathered through the D2L discussion tool allowed participants to read responses and reply if desired. Round One discussion responses were reformatted into statements, which were then rated through two successive rounds using a 1-5 Likert scale. Of the initial 142 statements, 91 statements were retained in the final round. Final statements were cross-referenced with the Flathead Watershed Sourcebook to identify learning objectives for the Flathead Watershed Educators Guide. Final statements identified the knowledge, skills, and dispositions deemed most important for students in the Flathead Watershed to learn. Statements supported the need for place-based watershed education in fostering positive attitudes toward conservation and protection of the natural environment.